FinO is an RNA chaperone that facilitates sense–antisense RNA interactions - Arthur, David C. (Oxford University Press, 2003)
The protein FinO represses F-plasmid conjugative transfer by facilitating interactions between the mRNA of the major F-plasmid transcriptional activator, TraJ, and an antisense RNA, FinP. FinO is known to bind stem–loop structures in both FinP and traJ RNAs; however, the mechanism by which FinO facilitates sense–antisense pairing is poorly understood. Here we show that FinO acts as an RNA chaperone to promote strand exchange and duplexing between minimal RNA targets derived from FinP. This strongly suggests that FinO may function to destabilize internal secondary structures within FinP and traJ RNAs that would otherwise act as a kinetic trap to sense–antisense pairing. The energy for FinO-catalyzed base-pair destabilization does not arise from ATP hydrolysis but appears to be supplied directly from FinO RNA binding free energy. An analysis of the activities of mutants that are specifically deficient in strand exchange but not RNA-binding activity demonstrates that strand exchange is essential to the ability of FinO to mediate sense–antisense RNA recognition, and that this function also plays a role in repression of conjugation in vivo.